Accent notation in Friedrich Kurschat’s German-Lithuanian and Lithuanian-German dictionaries - Strockis, Mindaugas (Baltistica, 2016)
The system of Lithuanian accent notation used in Friedrich Kurschat’s (in Lithuanian known as Fridrikis Kuršaitis) German-Lithuanian (1870, 1874) and Lithuanian-German (1883) dictionaries is very close to the modern accent orthography of Lithuanian, though it also displays certain differences. An important difference is the notation of secondary stresses. It reveals valid linguistic information about the reality of Lithuanian accentuation, neglected by the modern system of accent notation, as employed in modern dictionaries, schools, etc.
Keywords: Lithuanian accentuation; accent orthography; accent notation; secondary stress; Kurschat